2003
DOI: 10.1002/dvdy.10494
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and pigment cell defects in the lockjaw mutant reveal multiple roles for zebrafish tfap2a in neural crest development

Abstract: Members of the AP-2 transcription factor family have critical roles in many aspects of embryonic development. The zebrafish tfap2a mutant lockjaw (low) displays defects in skeletal and pigment cell derivatives of the neural crest. Here we show essential roles for tfap2a in subsets of embryonic cartilages and pigment cells. Defects in cartilage of the hyoid arch in low correlate with a loss of Hox group 2 gene expression and are suggestive of a transformation to a mandibular fate. In contrast, loss of joints in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 58 publications
5
89
3
Order By: Relevance
“…Our in situ hybridization experiments (Fig. 1B) showed that sox9b is expressed at high levels in premigratory neural crest about as early as other early crest markers such as foxd3 (formerly fkd6) (Odenthal and Nusslein-Volhard, 1998), snai1b (formerly snail2) (Thisse et al, 1995), and tfap2a (formerly AP2alpha) (Barrallo-Gimeno et al, 2004;Knight et al, 2003;Knight et al, 2004;O'Brien et al, 2004). Double in situ hybridization experiments with sox9b and either foxd3 or snai1b showed that these three genes are expressed in largely overlapping cell populations in this domain (data not shown).…”
Section: The Roles Of Sox9 In Otic Vesicle Developmentmentioning
confidence: 76%
See 2 more Smart Citations
“…Our in situ hybridization experiments (Fig. 1B) showed that sox9b is expressed at high levels in premigratory neural crest about as early as other early crest markers such as foxd3 (formerly fkd6) (Odenthal and Nusslein-Volhard, 1998), snai1b (formerly snail2) (Thisse et al, 1995), and tfap2a (formerly AP2alpha) (Barrallo-Gimeno et al, 2004;Knight et al, 2003;Knight et al, 2004;O'Brien et al, 2004). Double in situ hybridization experiments with sox9b and either foxd3 or snai1b showed that these three genes are expressed in largely overlapping cell populations in this domain (data not shown).…”
Section: The Roles Of Sox9 In Otic Vesicle Developmentmentioning
confidence: 76%
“…The transcription factor tfap2a is expressed early in crest development in zebrafish and other vertebrates (BarralloGimeno et al, 2004;Knight et al, 2004;Knight et al, 2003;Luo et al, 2003;O'Brien et al, 2004) (http://zfin.org). We examined tfap2a expression in zebrafish embryos homozygous for sox9a or sox9b mutations either singly or in double mutant combinations, and found no difference from wild type (data not shown), suggesting that sox9 genes are not upstream of tfap2a in zebrafish.…”
Section: Development 132 (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that the ectoderm imparts patterning on underlying NC cells. For example, AP-2 transcription factors are also required in ectoderm for patterning the craniofacial skeleton, and this interaction appears to involve Fgf signaling (Knight et al, 2003;Knight et al, 2004;Knight et al, 2005). Thus, future studies of cranial skeletal development and human craniofacial syndromes should focus more attention on the specialized epithelia of the facial ectoderm.…”
Section: Ectoderm As a Crucial Functional Source Of Edn1 In The Archesmentioning
confidence: 99%
“…tfap2a is a member of the AP-2 family of transcription factors, which play many important roles in embryonic development (Brewer et al, 2004;Eckert et al, 2005). Zebrafish tfap2a mutants display a loss of neural crest derivatives and a reduction in the expression of key NCC specifier genes (Knight et al, 2003;Barrallo-Gimeno et al, 2004;Knight et al, 2004). In double knockdowns of both tfap2a and its redundant family member tfap2c, early markers of NCC specification are lost at the NPB, including foxd3, snai1b and prdm1a (Li and Cornell, 2007).…”
Section: Introductionmentioning
confidence: 99%